Use of an electrolyte for aqueous fluorine ion batteries in the preparation of aqueous fluorine ion batteries

CN122931090APending Publication Date: 2026-10-16CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611407019.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但水系体系面临一系列严峻挑战:(1)氟离子电化学不稳定:F-具有极强的电负性,易与水分子形成强氢键(F-···H2O),不仅导致 F-自身活性下降,还会限制电池的工作电压

Benefits of technology

[0018] 1) This invention is the first to use BF4 with low fluoride ion concentration. - The electrolyte system suppresses HF generation at its source. This is achieved using BF4. - As a fluoride ion carrier, it slowly hydrolyzes in aqueous solution and releases low concentrations of free F in a controlled manner. - This avoids the high concentration of free F in the KF system. - The resulting side effects. Meanwhile, BF4... - The system significantly inhibits the generation of HF (hydrogen fluoride), thereby eliminating or greatly reducing the chemical corrosion and dissolution effects of HF on the positive and negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931090A_ABST
    Figure CN122931090A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of battery energy storage, and particularly relates to application of an electrolyte for a water-based fluorine ion battery in preparation of a water-based fluorine ion battery. ‑ Controllable hydrolysis releases low-concentration free F ‑ , and the acetate salt is used to construct a "proton-coupled fluorine ion buffer cycle" to actively regulate pH and promote hydrolysis equilibrium, thereby inhibiting HF corrosion and side reactions from the source. The battery using the system has a first-cycle specific capacity of 327.7 mAh g ‑1 , and no attenuation is observed after 50 cycles. The zinc symmetric battery is stably cycled for more than 1000 hours, significantly improving the electrode structure integrity and long-cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery energy storage technology, specifically relating to the application of an electrolyte for aqueous fluoride-ion batteries in the preparation of aqueous fluoride-ion batteries. Background Technology

[0002] With the growing global demand for high-energy-density and high-safety energy storage systems, traditional lithium-ion batteries are increasingly unable to meet the long-term development needs of large-scale energy storage and electric vehicles due to the scarcity of lithium resources, rising costs, and safety concerns associated with organic electrolytes. Against this backdrop, fluoride ion batteries (FIBs), with their unique electrochemical mechanisms and material advantages, are considered a strong contender for next-generation high-energy-density energy storage technology.

[0003] However, the development of fluoride-ion batteries has long been constrained by electrolyte bottlenecks. Early research on fluoride-ion batteries mostly used high-temperature solid electrolytes (such as LaF3, BaF2, etc.), but the operating temperature is usually above 150 °C, which limits their practical application. In order to reduce the operating temperature, researchers have tried to develop aqueous fluoride-ion batteries, using aqueous solutions as solvents to dissolve fluoride salts and achieve fluoride ion conduction at room temperature. However, the aqueous system faces a series of severe challenges: (1) Fluoride ion electrochemical instability: F - It has extremely high electronegativity and readily forms strong hydrogen bonds (F) with water molecules. - ...H2O), not only leading to F - The decrease in its own activity will also limit the working voltage of the battery. (2) Poor reversibility of the positive electrode reaction: the conversion-type positive electrode material represented by BiF3 undergoes Bi reaction during charging and discharging. 3+ The conversion of —Bi is accompanied by a huge volume expansion (over 100%), and the intermediate product Bi 3+ It is easily soluble in electrolyte, causing rapid capacity decay. (3) Severe hydrogen evolution corrosion of negative electrode: In aqueous electrolyte, hydrogen evolution reaction often occurs at zinc metal negative electrode (such as Zn + 2H2O → Zn(OH)2 + H2), which not only consumes active material, but the generated hydrogen may also cause gas expansion or even safety hazards.

[0004] To suppress the decomposition of water molecules, researchers have developed high-concentration salt strategies such as "water-in-salt" (WIS), which reduce the free water content by using large amounts of fluoride salts (such as KF), thereby widening the electrochemical window to above 3 V. These works have preliminarily verified the feasibility of aqueous fluoride ion electrochemistry, but most existing strategies rely on physical suppression of water decomposition, and the active regulation of the hydrolysis behavior of electrolyte components and their interfacial chemistry remains a blank.

[0005] Currently, existing technologies construct a KF / KOAc binary salt electrolyte system by introducing potassium acetate (KOAc) into an aqueous solution of potassium fluoride (KF). The core idea of ​​this approach is "hydrogen bond competition," that is, using high concentrations of OAc... - Ions and F - Competition for water molecules weakens F - Hydration. However, its regulation method is essentially a passive physical control, and does not involve active intervention in the chemical reactions of the electrolyte components themselves. The inherent high corrosivity defect of the KF electrolyte system is difficult to completely suppress. Summary of the Invention

[0006] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments.

[0007] As one aspect of the present invention, the present invention provides an application of an electrolyte for an aqueous fluoride-ion battery in the preparation of an aqueous fluoride-ion battery, wherein the electrolyte comprises a fluoroborate main salt, an acetate buffer salt and water as a solvent, wherein the concentration of the fluoroborate main salt is 0.1M~5M and the concentration of the acetate buffer salt is 0.5M~10M.

[0008] Preferably, the main salt of the fluoroborate is sodium tetrafluoroborate, and the buffer salt of the acetate is sodium acetate.

[0009] Preferably, the concentration of the fluoroborate main salt is 1M, and the concentration of the acetate buffer salt is 3M.

[0010] Preferably, the active material of the positive electrode of the aqueous fluorine-ion battery includes bismuth fluoride.

[0011] Preferably, the negative electrode of the aqueous fluoride-ion battery comprises metallic zinc.

[0012] Preferably, the solvent is water.

[0013] Preferably, the electrolyte is used between the zinc negative electrode and the bismuth fluoride positive electrode in an aqueous fluoride-ion battery, and the battery further includes a glass fiber separator for isolating the positive and negative electrodes.

[0014] Preferably, the positive electrode of the battery is prepared by the following method: bismuth fluoride, sodium alginate and Ketjen black are mixed in a mass ratio of (50~60):(10~20):(10~20), ground, water is added and stirred and ultrasonicated, the resulting slurry is coated on titanium foil, dried in an oven and then sliced.

[0015] Preferably, the electrolyte is prepared by a stepwise dissolution method: first, the acetate buffer salt is dissolved in water and stirred, then the fluoroborate main salt is added and stirred to obtain a colorless and transparent solution.

[0016] Preferably, the battery is assembled in an atmospheric environment, with the positive electrode in the positive electrode shell, electrolyte dripped onto the surface of the positive electrode, a glass fiber separator added, electrolyte dripped again, and then the negative electrode, gasket, spring and negative electrode shell placed, sealed and placed in a constant temperature oven.

[0017] The beneficial effects of this invention are:

[0018] 1) This invention is the first to use BF4 with low fluoride ion concentration. - The electrolyte system suppresses HF generation at its source. This is achieved using BF4. - As a fluoride ion carrier, it slowly hydrolyzes in aqueous solution and releases low concentrations of free F in a controlled manner. - This avoids the high concentration of free F in the KF system. - The resulting side effects. Meanwhile, BF4... - The system significantly inhibits the generation of HF (hydrogen fluoride), thereby eliminating or greatly reducing the chemical corrosion and dissolution effects of HF on the positive and negative electrode materials.

[0019] 2) This invention actively increases F by adjusting pH using NaOAc. - Concentration to optimize electrochemical performance.

[0020] To solve BF4 - To address the issue of insufficient reaction kinetics caused by excessively low fluoride ion concentration, this invention introduces NaOAc (sodium acetate) as a pH adjuster. NaOAc reacts with any trace amounts of HF that may be present in the system, converting it into CH3COOH / CH3COO. - Buffer pairs stabilize the electrolyte pH and simultaneously promote BF4 - Hydrolysis equilibrium shifts towards generating more free F - The direction of movement is adjusted to obtain a suitable and stable F. - The concentration is adjusted to achieve the optimal ratio of low side reactions and high reversibility.

[0021] 3) This invention achieves active protection of the electrode / electrolyte interface, suppressing the dissolution of positive and negative electrodes and side reactions.

[0022] Through the aforementioned synergistic effect, this invention constructs a "proton-coupled fluoride ion buffer cycle": CH3COO - Capture H + (From HF or water decomposition), producing CH3COOH; CH3COOH can then react with BF4 - The hydrolysis products interact, dynamically maintaining F. - The supply and pH are stable. This mechanism effectively inhibits the dissolution of the positive electrode active material, hydrogen evolution corrosion of the negative electrode, and chemical corrosion of the current collector, significantly improving the cycle stability and safety of the battery.

[0023] 4) Provides a universal and novel design paradigm for fluoride ion electrolytes: This invention not only solves the inherent defects of the KF system, but also pioneers a new paradigm based on BF4. - A novel pathway for aqueous fluoride-ion batteries with synergistic effects of salts and acetates. This system can be extended to other fluoroborates (such as KBF). 4、 Zn(BF4)2, NH4BF4, etc., and are compatible with a variety of cathode materials (such as BiF3, BiOF), providing a brand-new solution for the practical application of aqueous fluoride-ion batteries. Attached Figure Description

[0024] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below, wherein:

[0025] Figure 1 This is a comparison chart of the long-cycle performance of different electrodes.

[0026] Figure 2 This is a comparison chart of the rate performance of different electrodes.

[0027] Figure 3 For 0.1 mA cm -2 and 0.1 mAh cm -2 Voltage distribution diagram of Zn / / Zn symmetric cell in different electrolytes.

[0028] Figure 4 The cyclic voltammetry (CV) curves are for different electrodes.

[0029] Figure 5 Impedance spectroscopy (EIS) spectra of different electrodes.

[0030] Figure 6 A comparison of the tenth charge-discharge curves for different electrolytes.

[0031] Figure 7 For different electrolytes 1 1H NMR test results spectrum.

[0032] Figure 8 For different electrolytes 19 F NMR test results spectrum.

[0033] Figure 9 The images show the EDS elemental distribution of the initial electrode and the SEM images of the cathode morphology at different sizes.

[0034] Figure 10 The image shows a comparison of the positive electrode morphology after 10 cycles in 1 M NaBF4 and 1 M NaBF4 and 3 M NaOAc electrolytes.

[0035] Figure 11This is a comparison chart of the long-cycle performance of electrodes in different fluoroborate electrolytes.

[0036] Figure 12 Comparison of long-cycle performance of electrodes in electrolytes containing 1M sodium fluoroborate and 3M sodium acetate using different solvents.

[0037] Figure 13 Comparison of long-cycle performance of electrodes in 3M sodium acetate electrolyte with different fluoroborates. Detailed Implementation

[0038] To make the above-mentioned objectives, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to specific examples.

[0039] Example 1:

[0040] Preparation of positive and negative electrodes and electrolyte, and battery assembly:

[0041] 1. Preparation of cathode material: Mix BiF3, sodium alginate and Ketjen black in a mass ratio of 6:2:2.

[0042] 2. Preparation of positive electrode sheet: 0.2 g of the mixture was ground for 30 min, and 1200 μL of deionized water was added. The slurry was placed on a magnetic stirrer and stirred for 24 h to mix evenly. Then, it was sonicated for 10 min to remove air bubbles. After that, the slurry was evenly coated onto titanium foil using an automatic coating machine. Immediately afterwards, the titanium foil was transferred to an 80℃ oven and dried for 12 h. Then, the aluminum foil was cut into black circular positive electrode sheets using a manual slicing machine. The mass of active material in each electrode sheet (12 mm in diameter) was measured using a precision electronic balance. The amount of active material was approximately 1.8 mg.

[0043] 3. Preparation of negative electrode sheet: After repeatedly wiping the 0.1 mm thick zinc foil with ethanol, it is cut into circular electrode sheets with a diameter of 12 mm using a slicer.

[0044] 4. Electrolyte preparation: All chemical reagents were of analytical grade.

[0045] (1) Preparation of basic electrolyte (1 M KF): Accurately weigh a certain mass of potassium fluoride (KF), dissolve it in deionized water, stir magnetically until completely dissolved, and prepare a solution with a concentration of 1 mol / L. -1 A clear KF aqueous solution.

[0046] (2) Preparation of fluoroborate electrolyte: Weigh a certain amount of fluoroborate into a beaker, add a measured amount of deionized water, and stir magnetically at room temperature until a colorless and transparent homogeneous solution is obtained.

[0047] (3) Preparation of synergistic electrolyte (1 M NaBF4, 3 M NaOAc): First, weigh out sodium acetate of the corresponding concentration and dissolve it in deionized water. Stir at room temperature until completely dissolved to obtain a clear NaOAc aqueous solution. Then, add the measured amount of NaBF4 powder to the solution and stir magnetically at room temperature for at least 1 h to obtain a colorless and transparent homogeneous solution.

[0048] 5. Battery Assembly: Battery assembly was performed under normal atmospheric conditions, with insulated tweezers used throughout to prevent short circuits. First, the positive electrode shell was placed on a horizontal surface. Then, the positive electrode sheet, black side up, was placed in the center of the positive electrode shell. 50 μL of electrolyte was added to the surface of the positive electrode sheet. Next, a glass fiber separator was placed, followed by another 50 μL of electrolyte. The negative electrode was then placed in the center, and finally, the gasket, spring, and negative electrode shell were placed in sequence. With the negative electrode facing up, the battery was sealed internally for 30 seconds under a sealing pressure of 5 MPa to obtain the assembled battery. After standing in a 30°C constant temperature oven for 2 hours, normal electrochemical testing was performed.

[0049] Example 2:

[0050] Electrochemical performance testing of the optimal electrolyte:

[0051] The battery was assembled according to the method described in Example 1. The electrochemical performance of the 1 M NaBF4 and 3 M NaOAc electrolyte system was tested and compared with that of the 1 M NaBF4 and 1 M KF systems.

[0052] 1. Long-cycle performance ( Figure 1 At a 0.5 C rate, the first-cycle discharge specific capacity of the 1 M NaBF4 and 3 M NaOAc system reaches as high as 327.7 mAh g⁻¹. -1 After 50 cycles, the capacity showed almost no decay, and the coulombic efficiency was close to 100%. The 1 M NaBF4 system, after experiencing rapid capacity decay in the first 10 cycles, stabilized at approximately 100 mAh g⁻¹. -1 The platform; however, the capacity of the 1 M KF system has continued to decline to almost zero.

[0053] 2. Ratio performance ( Figure 2 The 1 M NaBF4 and 3 M NaOAc system exhibited excellent capacity retention as the current density gradually increased from 0.1 C to 3 C, maintaining a discharge capacity close to that at 0.1 C even at a high rate of 3 C. When the current density returned to 0.1 C, the capacity rapidly recovered to nearly 300 mAh g⁻¹. -1 It is far superior to the other two systems.

[0054] 3. Zinc-symmetric battery cycle ( Figure 3The 1 M NaBF4 and 3 M NaOAc systems not only exhibited lower deposition / dissolution overpotentials but also achieved ultra-long stable cycling exceeding 1000 hours. Short circuits occurred after more than 200 hours of cycling in the 1 M NaBF4 system, while in the 1 M KF electrolyte, short circuits occurred due to dendrite formation after approximately 20 hours.

[0055] 4. Cyclic Voltammetry (CV) Test Figure 4 ) and impedance testing ( Figure 5 The redox peak current densities of the 1 M NaBF4 and 3 M NaOAc systems were significantly higher than those of the 1 M NaBF4 and 1 M KF systems, and the peak potential spacing was smaller, indicating that the reaction has high reversibility and fast kinetics. Impedance fitting showed that its charge transfer impedance (Rct) was significantly lower than that of the other systems, indicating that the interfacial fluoride ion conversion reaction has a lower energy barrier.

[0056] 5. Charge-discharge curves ( Figure 6 In the tenth charge-discharge curve, the Zn(BF4)2 system has no obvious plateau, the capacity is almost zero, and a short circuit occurs. The 1 M NaBF4 system has a low capacity. The 1 M NaBF4 and 3 M NaOAc systems have the flattest and most reversible charge-discharge plateaus.

[0057] 6. NMR spectral analysis ( Figure 7 , Figure 8 ): 1 1H NMR showed that acetate ions interacted with water molecules; 19 FNMR confirmed that the addition of acetate promoted the BF4 generation. - Hydrolysis was observed in the spectrum, representing BF4. - (-151 ppm) and free F - The peak at -120 ppm indicates that fluoride ion release is promoted.

[0058] Example 3:

[0059] Comparative Test:

[0060] 1. Electrolyte cation screening ( Figure 11 , Figure 13 The NaBF4, KBF4, NH4BF4, and Zn(BF4)2 systems (with or without 3M NaOAc) were compared at a 0.5 C rate. The results showed that the NaBF4 and NaOAc systems exhibited both high stable specific capacity (approximately 327 mAh g⁻¹). -1The system exhibits near 100% coulombic efficiency and optimal cycle stability; the KBF4 and NH4BF4 systems have relatively low specific capacities; the Zn(BF4)2 system is too acidic, and its specific capacity rapidly decays to zero. This indicates that Na... + When used as the main cation, its electrochemical performance is far superior to that of K. + Zn 2+ NH4 + .

[0061] 2. Test on the effect of different solvents ( Figure 12 When the solvent is deionized water, the battery's first-cycle specific capacity is approximately 327.7 mAh g. -1 It exhibits excellent cycle stability; however, when using a solvent mixture of deionized water and ethanol in equal proportions, the initial specific capacity is lower, the capacity decays rapidly, and the coulombic efficiency is only maintained at around 50%. Therefore, the optimal solvent is deionized water.

[0062] 3. Electrode microstructure testing ( Figure 9 , Figure 10 ): Figure 9 The results in step a show that the material is composed of aggregated primary particles with sizes ranging from 1 to 10 micrometers, exhibiting irregular shapes and smooth surfaces. Energy dispersive spectroscopy (EDS) mapping analysis confirmed the material's uniform composition at the microscale, laying the foundation for subsequent uniform electrochemical reactions. Further magnification revealed… Figure 9 In image b, the relatively smooth surfaces of these micron-sized primary particles can be seen more clearly. High-magnification magnification of a single representative particle reveals its surface details. Figure 9 (c) To reveal the structure of the material's conductive network, we performed higher-resolution observations of the particle ( Figure 9 (d) At the nanoscale, numerous smaller particles, ranging in size from tens to two hundred nanometers, can be observed densely attached to the surface of micron-sized particles. These nanoparticles are believed to be the active material BiF3. This indicates that the material has a low intrinsic electronic conductivity and a long ion diffusion path, placing higher demands on the ion transport and interfacial reaction kinetics of the electrolyte.

[0063] Figure 10 The BiF3 electrode was observed using scanning electron microscopy (SEM) after 10 cycles. Figure 10As shown in Figure a, the electrode exhibits severe structural damage after cycling in 1 M NaBF4 electrolyte. Its surface is covered with large, crisscrossing cracks that penetrate the entire electrode sheet, leading to a loose and fragmented electrode structure. This morphological feature is a direct result of the combined effects of internal chemical and electromechanical stresses. These cracks irreversibly disrupt the electronic conduction pathways within the electrode and continuously expose fresh electrode material to the corrosive electrolyte, thus accelerating capacity decay and failure. In contrast, Figure 10 The electrode surface of sample b maintained high structural integrity after cycling in a 1 M NaBF4 and 3 M NaOAc co-electrolyte. The electrode morphology was dense and smooth, with no obvious cracking or peeling observed. This intact microstructure is a direct manifestation of the successful protection of the electrode by the proton-coupled fluoride ion buffering mechanism. This mechanism maintains the electrode / electrolyte interface environment at a near-neutral level for a long time, fundamentally eliminating the chemical corrosion of the active material by the acidic medium and preserving the mechanical integrity of the material.

[0064] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. The application of an electrolyte for aqueous fluoride-ion batteries in the preparation of aqueous fluoride-ion batteries, characterized in that, The electrolyte comprises a fluoroborate main salt, an acetate buffer salt, and water as a solvent. The concentration of the fluoroborate main salt is 0.1M to 5M, and the concentration of the acetate buffer salt is 0.5M to 10M.

2. The application according to claim 1, characterized in that, The main salt of the fluoroborate is sodium tetrafluoroborate, and the buffer salt of the acetate is sodium acetate.

3. The application according to claim 1 or 2, characterized in that, The concentration of the fluoroborate main salt is 1M, and the concentration of the acetate buffer salt is 3M.

4. The application according to claim 1 or 2, characterized in that, The active material of the positive electrode of the aqueous fluoride-ion battery includes bismuth fluoride.

5. The application according to claim 1 or 2, characterized in that, The negative electrode of the aqueous fluoride-ion battery includes metallic zinc.

6. The application according to claim 1 or 2, characterized in that, The solvent is water.

7. The application according to claim 4, characterized in that, The electrolyte is used between the zinc negative electrode and the bismuth fluoride positive electrode in an aqueous fluoride-ion battery, and the battery also includes a glass fiber separator for isolating the positive and negative electrodes.

8. The application according to claim 4, characterized in that, The positive electrode of the battery is prepared by the following method: bismuth fluoride, sodium alginate and Ketjen black are mixed in a mass ratio of (50~60):(10~20):(10~20), ground, water is added and stirred and ultrasonicated, the resulting slurry is coated on titanium foil, dried in an oven and then sliced.

9. The application according to claim 8, characterized in that, The electrolyte is prepared by a stepwise dissolution method: first, the acetate buffer salt is dissolved in water and stirred, then the fluoroborate main salt is added and stirred to obtain a colorless and transparent solution.

10. The application according to claim 9, characterized in that, The battery is assembled in an atmospheric environment. The positive electrode is placed in the positive electrode shell, and electrolyte is dropped onto the surface of the positive electrode. After adding a glass fiber separator, electrolyte is dropped again. Then, the negative electrode, gasket, spring sheet and negative electrode shell are placed, sealed and placed in a constant temperature oven.